Pengaruh Faktor-Faktor Fraud Diamond Dalam Mendeteksi Financial Statement Fraud - Almira Nadia Calista; Arief Himmawan Dwi Nugroho (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to determine the effect of pressure, opportunity, rationalization and capability on Financial Statement Fraud. The sampling of this research is purposive sampling. The sample of this research is manufacturing companies in the basic and chemical sectors listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The test method in this study is panel data regression analysis. The results of this study indicate that external pressure has a significant negative effect on financial statement fraud. Meanwhile, personal financial need, ineffective monitoring, auditor change and changes of directors have no significant effect on the variable of financial statement fraud. The results of this study are expected to be a reference for future research and other users of financial statement information in detecting financial statement fraud.